Optimization and techno-economic-environmental analysis of a grid-tied hybrid renewable energy system for a subtropical Indian University - Akhlaque Ahmad Khan; Ahmad Faiz Minai; Abdullatif Hakami; Mohammed Alkahtani; Hasmat Malik (Discover Sustainability)
Abstract The utilization of solar-powered electricity represents a highly effective strategy for enhancing renewable energy generation in India. The abundant energy from solar radiation and the decreasing costs of PV modules have led to an increased demand for grid-tied PV power plants (GTPV-PP). This study outlines a net metering strategy for a university building in Lucknow, which utilizes GTPV-PPs and the HOMER-Pro (V-3.16.2 model) to meet the building's electricity needs. This version of HOMER determines the most economical setup, evaluates unprocessed data, and creates a demand cycle using load survey data. Furthermore, this software evaluates various scenarios, including both grid-tied and off-grid options, depending on the availability of renewable energy sources (RESs). The HOMER Pro program subsequently simulated these scenarios over the course of a year, utilizing economic and technical data as input. The results indicate that the most economical and eco-friendly design consists of a 100-kW solar photovoltaic system connected to a 100-kW converter and integrated with the utility grid. We project the system to last for 25 years, with an estimated levelized cost of energy (LCOE) of 0.0404 USD/kWh and a net present cost (NPC) of 104.598 thousand USD. The estimated payback period (PBP) is around 6 years. The optimized system significantly reduces carbon dioxide emissions, with a reduction of 101.875 tons compared to the existing grid and 243.244 tons compared to diesel generator (DG) systems. This reduction is attributed to its renewable component, which accounts for 59.70% of the total emissions.